2016
DOI: 10.1177/0884533615627157
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition Status Parameters and Hydration Status by Bioelectrical Impedance Vector Analysis Were Associated With Lung Function Impairment in Children and Adolescents With Cystic Fibrosis

Abstract: The CFG exhibited a compromised nutrition status assessed by anthropometric and BIA parameters. Nutrition screening, anthropometric and BIA parameters, and hydration status were associated with lung function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 55 publications
1
16
0
Order By: Relevance
“…The total number of patients with CF and controls was 1839 and 2178, respectively. The age range of the subjects was different between the studies: Nine studies recruited subjects age <10 y [18,22,40] and 10 studies included subjects age 10 y to 20 y [17,39,49] but the majority of the studies were conducted in adult populations (18 studies: age ≥20 y; Table 1). Only one study recruited both children and adults [26].…”
Section: Description and Quality Of The Studiesmentioning
confidence: 99%
“…The total number of patients with CF and controls was 1839 and 2178, respectively. The age range of the subjects was different between the studies: Nine studies recruited subjects age <10 y [18,22,40] and 10 studies included subjects age 10 y to 20 y [17,39,49] but the majority of the studies were conducted in adult populations (18 studies: age ≥20 y; Table 1). Only one study recruited both children and adults [26].…”
Section: Description and Quality Of The Studiesmentioning
confidence: 99%
“…CF is characterized by elevated sweat chloride levels (SCL), pancreatic insufficiency (PI), respiratory disease with a progressive decline of lung function, chronic bacterial infections of lower airways and sinuses and male infertility because of obstructive azoospermia . Such symptoms represent the eye pit of a more complex, systemic syndrome that includes alterations of metabolism and functions of adipose, muscle and other tissues, body mass index (BMI), and pathways related to glucose, lipids and liposoluble vitamins, in particular vitamin D …”
Section: Introductionmentioning
confidence: 99%
“…Five studies compared BIA and SF, 1 study compared SF with DD, and another one to near‐infrared interactance and ADP; the study found that none of the SF equations agreed with ADP in females with CF . De Waele et al concluded that radial peripheral quantitative computed tomography (pQCT) might help to identify patients with CF with a normal BMC, but it cannot replace DXA as a diagnostic tool .…”
Section: Resultsmentioning
confidence: 99%
“…Combined methods to assess BC. The main aims of these studies in combining different methods were to (1) validate a BC method against an established reference (12 studies) 10,11,22,25,27,31,[75][76][77][78][79][80] and/or evaluate the agreement between different methods (11 studies) 32,37,38,40,[81][82][83][84][85][86] without specifying a reference BC method and (2) combine different methods (14 studies) 23,26,44,53,55,[87][88][89][90][91][92][93][94][95] to have a more precise BC evaluation. Table S1 in the supplementary material shows the characteristics, main aims, and findings of these studies.…”
Section: Methods For Bc Assessmentmentioning
confidence: 99%